Tanggung Jawab Pemerintah Daerah Kota Pekanbaru Terhadap Perlindungan Anak Terlantar Berdasarkan Peraturan Daerah Provinsi Riau Nomor 3 Tahun 2013 Tentang Perlindungan Hak Dasar Anak - Jessy Rhoudatul Aulia; Emilda Firdaus; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Homeless children are children who spend most of their time doing daily living activities on thestreets, to make a living or roam the streets and other public places. One of the social welfare problems thatare still flourish in Pekanbaru today is homeless children. Children are the next generation the ideals of thestruggle of a nation that has s strategic role and have special characteristics and properties that areexpected to ensure the continued existence of the nation and the state in the future.given the position andhope to the children as the potential and future of the nation so that the child may deserve the attention ofall parties so that children can grow and develop naturally and avoid the treatment and the wrong action,violence, discrimination which would undermine the development of the child, wheter physical, mental, andsocial development.This research is motivated by the high number of homeless children in Pekanbaru City so the authorconsiders it’s important to know how the responsibility of the provincial government for the protection ofhomeless children, what causes the number of homeless children in Pekanbaru City, and what are the effortsof the provincial government in overcoming the number of homeless children in Pekanbaru City. This studyuses Riau Province Regional Regulation Number 3 of 2013 about the Protection of Children’s Basic Rightswhich has 4 (four) indicators, namely: 1. Social Rehabilitation; 2. Mentoring; 3. Empowerment; and 4.Social Assistance. Based on this regional regulation, the authors obtained research results that: 1. Theimplementation of the protection of homeless children is still not optimal; 2. Obstacles in implementing theprotection of homeless children, namely the limited resources owned by the City of Pekanbaru, both humanresources and non-human resources.This research was conducted at Pekanbaru Departement of Human Service and Riau Departement ofHuman Service, while the population and samples were all parties related to the problems studied in thisstudy. The data collection methods used in this study were observation, interviews, questionnaires, andliterature study. Sourcec of data used are primary data, secondary data, and tertiary data.Keywords: Responsibility, Protection, Homeless Children.